Production process of high-purity pitting-corrosion-resistant Ni-Fe-Cr-Mo-Cu-based corrosion-resistant alloy
Through electric furnace + AOD + LF + electroslag smelting process and composition adjustment, combined with forging and solid solution treatment, the problem of 0Cr23Ni40Mo3Cu2Ti alloy not being corrosion resistant in Cl- ion corrosion was solved, and high-purity, pitting corrosion-resistant Ni-Fe- The production of Cr-Mo-Cu based corrosion-resistant alloys meets strict corrosion performance standards.
Patent Information
- Application Number
- CN202411487359.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-24
AI Technical Summary
The existing 0Cr23Ni40Mo3Cu2Ti alloy is not corrosion resistant during Cl-ion corrosion, and the addition of N elements will affect the purity of the molten steel, making it difficult to produce high-purity and pitting-resistant materials.
The process of using electric furnace+AOD+LF+electric residue is used to smelter. By adjusting the ingredients and controlling the types of dehydration agent, it ensures CR+3.3MO+0.25NI ≥ 41.5, C ≤ 0.015 %, N ≤100PPM, to obtain 0CR23NI40MO3CU2Ti 3CU2TI electric slag that meets the standard requirements. Ingots, and solid-soluble treatment of forging, rolling, and 980 ° C, prepare high-purity, erosion-resistant NI-Fe-CR-MO-CU base corrosion-resistant alloys.
It achieves high purity and pitting corrosion resistance with pitting corrosion rate ≤0.5g/m2, inclusions ≤1.0, and carbonitrides ≤2.0 in Cl-ion corrosion environment, and meets the requirements of ASTM G48 standard method A corrosion test. .
Smart Images

Figure CN119351851A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alloy smelting, and in particular to a production process of a high-purity, pitting-resistant Ni-Fe-Cr-Mo-Cu-based corrosion-resistant alloy. Background Art
[0002] 0Cr23Ni40Mo3Cu2Ti alloy contains high Ni and Cr elements, and is generally considered to be resistant to oxide stress corrosion and oxidation-reduction composite medium corrosion, such as sulfuric acid or nitric acid corrosion. However, this type of steel is generally considered to be not resistant to Cl- ion corrosion, that is, not resistant to pitting corrosion. Using ASTM G48 standard A method for corrosion, after 24 hours of corrosion at room temperature, the general corrosion rate is ≥1g / m2.
[0003] At present, pitting corrosion resistant materials generally require high corrosion resistance coefficient (PREN = Cr + 3.3Mo + 16N), so pitting corrosion resistant materials are generally duplex steels such as S32205 and S32750 and super austenitic stainless steels such as S31254. However, these grades have poor corrosion performance in oxidizing acids.
[0004] Since 0Cr23Ni40Mo3Cu2Ti contains a high content of Ti, if more N is added, a large amount of titanium carbonitride will be formed, which will affect the purity of molten steel. Therefore, it is an urgent problem for technicians to produce a high-purity, pitting-resistant 0Cr23Ni40Mo3Cu2Ti alloy material. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a production process of a high-purity, pitting-resistant Ni-Fe-Cr-Mo-Cu based corrosion-resistant alloy, which can produce a high-purity, pitting-resistant 0Cr23Ni40Mo3Cu2Ti alloy material.
[0006] In order to solve the above technical problems, the technical solutions adopted by the present invention are as follows.
[0007] A production process of a high-purity, pitting-resistant Ni-Fe-Cr-Mo-Cu-based corrosion-resistant alloy comprises the following steps:
[0008] S1. Determine the composition control point of the corrosion-resistant alloy;
[0009] S2. The raw materials are smelted in an electric furnace + AOD furnace + LF furnace to obtain φ250-430mm electrode blanks;
[0010] S3. The electrode blank is remelted by electroslag in a protective atmosphere, and the electroslag ingot with a diameter of 360-590 mm is obtained by constant melting rate electroslag.
[0011] Preferably, the composition control point in step S1 is specifically: the control elements simultaneously satisfy Cr+3.3Mo+0.25Ni≥41.5, C≤0.015%, and N≤100ppm.
[0012] Preferably, the raw materials in step S2 include the following components in weight percentage: Cr22.8-23.2%, Ni38.8-39.2%, Mo3.0-3.2%, Cu1.8-2.2%, C≥2.0%, P≤0.025%.
[0013] Preferably, the step S2 specifically includes the following steps:
[0014] S21. Electric furnace smelting: adjust C to ≥ 2.00%;
[0015] S22.AOD furnace smelting: Blow oxygen until C≤0.006% and then reduce, adjust each element to the internal control range;
[0016] S23.LF furnace smelting: Al wire and Al powder are used as deoxidizers for deoxidation; Ar gas is used for stirring during smelting, and Ca wire is inserted at 3 meters / ton before steelmaking; casting is carried out after the composition is qualified, and the casting temperature is controlled at 1500-1530℃ to obtain φ250-430mm electrode blanks.
[0017] Preferably, in step S23, 0.5-1.0 kg of deoxidizer is added per ton of molten steel.
[0018] Preferably, the protective atmosphere in step S3 is Ar gas, the electroslag adopts a 5-element slag system, the slag system is CaF2:Al2O3:CaO:MgO:TiO2=50:22:20:5:3, and the slag system controls C≤0.03%; the melting rate of the φ360mm electroslag ingot is controlled at 5.5±0.5kg / min, the melting rate of the φ480mm electroslag ingot is controlled at 6.5±0.5kg / min, and the melting rate of the φ590mm electroslag ingot is controlled at 8±0.5kg / min.
[0019] Preferably, the step S3 further includes the following steps:
[0020] S4. The electroslag ingot is prepared into the required specifications by forging or rolling, and is subjected to a solid solution treatment at 980°C to obtain a high-purity, pitting-resistant Ni-Fe-Cr-Mo-Cu based corrosion-resistant alloy.
[0021] Due to the adoption of the above technical scheme, the technical progress achieved by the present invention is as follows.
[0022] The present invention adopts the process of electric furnace + AOD + LF + electroslag for smelting, and obtains 0Cr23Ni40Mo3Cu2Ti electroslag ingots meeting the standard requirements by adjusting the composition, controlling the type of deoxidizer, etc., and prepares forgings and rolled materials of relatively specifications through forging or rolling, and then solid-solution is carried out at 980°C to obtain 0Cr23Ni40Mo3Cu2Ti forgings, which are corroded by ASTM G48 standard A method, with a corrosion time of 24h, a corrosion temperature of 22±2°C, and a pitting corrosion rate of ≤0.5g / m 2 , and inclusions ≤1.0 level, carbonitrides ≤2.0 level. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The metallographic diagram of the first corrosion-resistant alloy prepared by the present invention;
[0024] Figure 2 The metallographic diagram of the second corrosion-resistant alloy prepared by the present invention;
[0025] Figure 3 This is the metallographic phase diagram of the third corrosion-resistant alloy prepared by the present invention. DETAILED DESCRIPTION
[0026] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.
[0027] A production process of a high-purity, pitting-resistant Ni-Fe-Cr-Mo-Cu-based corrosion-resistant alloy comprises the following steps:
[0028] S1. Determine the composition control point of corrosion-resistant alloy.
[0029] Specifically as shown in Table 1, Cr, Ni, Mo, and C are important elements that affect the pitting corrosion performance of alloy materials, and the controlling elements simultaneously satisfy Cr+3.3Mo+0.25Ni≥41.5, C≤0.015% (the lower the better), and N≤100ppm (the lower the better).
[0030]
[0031] Table 1 Composition control points of corrosion-resistant alloys
[0032] S2. The raw materials are smelted in an electric furnace + AOD furnace + LF furnace to obtain φ250-430mm electrode blanks.
[0033] The raw materials include the following components in weight percentage: Cr 22.8-23.2%, Ni 38.8-39.2%, Mo 3.0-3.2%, Cu 1.8-2.2%, C≥2.0%, and P≤0.025%.
[0034] This step specifically includes the following steps:
[0035] S21. Electric furnace smelting: adjust C to ≥2.00% to provide conditions for subsequent AOD oxygen blowing and also help control ultra-low N content.
[0036] S22.AOD furnace smelting: Blow oxygen until C≤0.006% before reduction can be carried out, and elements such as Cr, Ni, Mo, and Cu need to be adjusted to the internal control range.
[0037] Adjust elements such as Cr, Ni, Mo, Cu, etc. to the internal control range. Specifically, adjust by adding pure metals or alloys containing corresponding elements, such as high chromium, nickel plates, etc.
[0038] S23.LF furnace smelting: Al wire and Al powder are used as deoxidizers for deoxidation. SiCa powder is prohibited for deoxidation to prevent carbon increase. Ar gas is used for stirring during smelting, and Ca wire is inserted at 3 meters / ton before steelmaking to prevent oxygen increase during casting. After the composition is qualified and the temperature is appropriate, casting is carried out in time. The casting temperature is controlled at 1500-1530℃ to obtain φ250-430mm electrode blanks.
[0039] Specifically, 0.5-1.0 kg of deoxidizer is added per ton of molten steel.
[0040] S3. The electrode blank is remelted by electroslag in a protective atmosphere, and the electroslag ingot with a diameter of 360-590 mm is obtained by constant melting rate electroslag.
[0041] Specifically, the protective atmosphere is Ar gas; the electroslag adopts a 5-element slag system, the slag system is CaF2:Al2O3:CaO:MgO:TiO2=50:22:20:5:3, and the slag system controls C≤0.03%; the melting rate of the φ360mm electroslag ingot is controlled at 5.5±0.5kg / min, the melting rate of the φ480mm electroslag ingot is controlled at 6.5±0.5kg / min, and the melting rate of the φ590mm electroslag ingot is controlled at 8±0.5kg / min. Because the current and voltage used by electroslag ingots of different specifications are different, this process is controlled by melting rate instead of current and voltage.
[0042] S4. The electroslag ingot is prepared into the required specifications by forging or rolling, and is subjected to a solid solution treatment at 980°C to obtain a high-purity, pitting-resistant Ni-Fe-Cr-Mo-Cu based corrosion-resistant alloy.
[0043] The corrosion-resistant alloy material prepared by the present invention can meet the following requirements: ① The corrosion-resistant alloy material is corroded by ASTM G48 standard A method, and after 24 hours of corrosion at 22±2°C, the pitting corrosion rate is ≤0.5g / m 20Cr23Ni40Mo3Cu2Ti material; ② The corrosion-resistant alloy material is tested for inclusions according to GB / T 10561A method, and the inclusion levels are ≤1.0 and the carbonitrides are ≤2.0.
[0044] The present invention can obtain excellent carbonitride materials with high purity by controlling the composition and low nitrogen, and low carbon control, and control Cr+3.3Mo+0.25Ni≥41.5, and can obtain 0Cr23Ni40Mo3Cu2Ti materials with good pitting resistance and high purity. The specific principle of good pitting resistance is as follows:
[0045] According to the pitting corrosion calculation formula: PREN = Cr + 3.3Mo + 16N, generally speaking, the higher the PREN value, the better the pitting corrosion resistance, that is, the higher the control of the three elements Cr, Mo, and N, the better the pitting corrosion resistance of the steel; in addition, the better the purity of the molten steel, the better its corrosion resistance. Since 0Cr23Ni40Mo3Cu2Ti steel contains a large amount of Ti, if its N element is controlled too high, a large amount of carbon nitride will be formed, resulting in a carbonitride rating exceeding level 2.0, and pitting pits will also be formed during the corrosion process, thereby affecting the corrosion resistance of the material. Therefore, it is proposed that for Ti-containing steels such as 0Cr23Ni40Mo3Cu2Ti, its N content should be low-controlled, and its corrosion resistance can be improved by using Cr, Mo, and Ni elements in stainless steel. In addition, when conducting corrosion tests, the data measured for the same composition also fluctuate. It is not only when Cr+3.3Mo+0.25Ni≥41.5 that its pitting corrosion performance can meet ≤0.5g / m 2 , but 0Cr23Ni40Mo3Cu2Ti steel meets Cr+3.3Mo+0.25Ni≥41.5, and its pitting corrosion performance meets ≤0.5g / m 2 .
[0046] Embodiment 1
[0047] S1. Determine the composition control point of corrosion-resistant alloy.
[0048] The specific composition control points are: the control elements simultaneously satisfy Cr+3.3Mo+0.25Ni=41.5, C=0.015%, and N=100ppm.
[0049] S2. The raw materials are smelted in an electric furnace + AOD furnace + LF furnace to obtain φ250-430mm electrode blanks.
[0050] The raw materials include the following components in weight percentage: Cr is 23.2%, Ni is 39.2%, Mo is 3.2%, Cu is 2.2%, C is 2.00%, and P is 0.025%.
[0051] S21. Electric furnace smelting: adjust C to 2.00%.
[0052] S22. AOD furnace smelting: Blow oxygen until C=0.006% and then perform reduction to adjust each element to the internal control range.
[0053] S23.LF furnace smelting: Al wire and Al powder are used as deoxidizers for deoxidation, and 1.0kg of deoxidizer is added for every ton of molten steel; Ar gas is used for stirring during smelting, and Ca wire is inserted at 3 meters / ton before tapping; after the composition is qualified and the temperature is appropriate, casting is carried out, and the casting temperature is controlled at 1530℃ to obtain φ250-430mm electrode billets.
[0054] S3. The electrode blank is remelted by electroslag in a protective atmosphere, and the electroslag ingot with a diameter of 360-590 mm is obtained by constant melting rate electroslag.
[0055] The protective atmosphere is Ar gas; the electroslag adopts a 5-element slag system, the slag system is CaF2:Al2O3:CaO:MgO:TiO2=50:22:20:5:3, and the slag system controls C=0.03%; the melting rate of the φ360mm electroslag ingot is controlled at 6kg / min, the melting rate of the φ480mm electroslag ingot is controlled at 7kg / min, and the melting rate of the φ590mm electroslag ingot is controlled at 8.5kg / min. The final composition of the electroslag ingot is C0.014%, Cr23.22%, Ni39.18%, Mo3.23%, Cu2.22%, P0.025%, and N97ppm.
[0056] S4. The electroslag ingot is prepared into the required specifications by forging or rolling, and is subjected to a solid solution treatment at 980°C to obtain a high-purity, pitting-resistant Ni-Fe-Cr-Mo-Cu based corrosion-resistant alloy.
[0057] The specific pitting corrosion rate and the levels of inclusions and carbonitrides of the corrosion-resistant alloy prepared in Example 1 under the conditions of corrosion time of 24 h and corrosion temperature of 22±2° C. are shown in Table 2 below:
[0058]
[0059] Table 2
[0060] Embodiment 2
[0061] S1. Determine the composition control point of corrosion-resistant alloy.
[0062] The specific composition control points are: the control elements simultaneously satisfy Cr+3.3Mo+0.25Ni=42, C=0.01%, and N=95ppm.
[0063] S2. The raw materials are smelted in an electric furnace + AOD furnace + LF furnace to obtain φ250-430mm electrode blanks.
[0064] The raw materials include the following components in weight percentage: Cr is 23.0%, Ni is 39.0%, Mo is 3.1%, Cu is 2.0%, C is 2.05%, and P is 0.02%.
[0065] S21. Electric furnace smelting: adjust C to 2.05%.
[0066] S22. AOD furnace smelting: Blow oxygen until C=0.005% and then carry out reduction, and adjust each element to the internal control range.
[0067] S23.LF furnace smelting: Al wire and Al powder are used as deoxidizers for deoxidation, and 1.0kg of deoxidizer is added for every ton of molten steel; Ar gas is used for stirring during smelting, and Ca wire is inserted at 3 meters / ton before tapping; after the composition is qualified and the temperature is appropriate, casting is carried out, and the casting temperature is controlled at 1520℃ to obtain φ250-430mm electrode billets.
[0068] S3. The electrode blank is remelted by electroslag in a protective atmosphere, and the electroslag ingot with a diameter of 360-590 mm is obtained by constant melting rate electroslag.
[0069] The protective atmosphere is Ar gas; the electroslag adopts a 5-element slag system, the slag system is CaF2:Al2O3:CaO:MgO:TiO2=50:22:20:5:3, and the slag system controls C=0.02%; the melting rate of the φ360mm electroslag ingot is controlled at 5.5kg / min, the melting rate of the φ480mm electroslag ingot is controlled at 6.5kg / min, and the melting rate of the φ590mm electroslag ingot is controlled at 8.0kg / min. The final electroslag ingot composition is C0.012%, Cr22.95%, Ni39.05%, Mo3.15%, Cu2.04, P0.019%, N89ppm.
[0070] S4. The electroslag ingot is prepared into the required specifications by forging or rolling, and is subjected to a solid solution treatment at 980°C to obtain a high-purity, pitting-resistant Ni-Fe-Cr-Mo-Cu based corrosion-resistant alloy.
[0071] The specific pitting corrosion rate and the levels of inclusions and carbonitrides of the corrosion-resistant alloy prepared in Example 2 under the conditions of corrosion time of 24 h and corrosion temperature of 22±2° C. are shown in Table 3 below:
[0072]
[0073] Table 3
[0074] Embodiment 3
[0075] S1. Determine the composition control point of corrosion-resistant alloy.
[0076] The specific composition control points are: the control elements simultaneously satisfy Cr+3.3Mo+0.25Ni=42.5, C=0.005%, and N=90ppm.
[0077] S2. The raw materials are smelted in an electric furnace + AOD furnace + LF furnace to obtain φ250-430mm electrode blanks.
[0078] The raw materials include the following components in weight percentage: Cr is 22.8%, Ni is 38.8%, Mo is 3.0%, Cu is 1.8%, C is 2.1%, and P is 0.015%.
[0079] S21. Electric furnace smelting: adjust C to 2.1%.
[0080] S22. AOD furnace smelting: Blow oxygen until C=0.004% and then carry out reduction, and adjust each element to the internal control range.
[0081] S23.LF furnace smelting: Al wire and Al powder are used as deoxidizers for deoxidation, and 1.0kg of deoxidizer is added for every ton of molten steel; Ar gas is used for stirring during smelting, and Ca wire is inserted at 3 meters / ton before tapping; after the composition is qualified and the temperature is appropriate, casting is carried out, and the casting temperature is controlled at 1500℃ to obtain φ250-430mm electrode billets.
[0082] S3. The electrode blank is remelted by electroslag in protective atmosphere, and the electroslag is kept at a constant melting rate to obtain φ360-590mm electroslag ingots. The protective atmosphere is Ar gas; the electroslag adopts a 5-element slag system, the slag system is CaF2:Al2O3:CaO:MgO:TiO2=50:22:20:5:3, and the slag system is controlled to be C=0.01%; the melting rate of the φ360mm electroslag ingot is controlled at 5.0kg / min, the melting rate of the φ480mm electroslag ingot is controlled at 6.0kg / min, and the melting rate of the φ590mm electroslag ingot is controlled at 7.5kg / min. The final electroslag ingot composition is C0.007%, Cr22.82%, Ni38.78%, Mo2.97%, Cu1.84, P0.016%, N87ppm.
[0083] S4. The electroslag ingot is prepared into the required specifications by forging or rolling, and is subjected to a solid solution treatment at 980°C to obtain a high-purity, pitting-resistant Ni-Fe-Cr-Mo-Cu based corrosion-resistant alloy.
[0084] The specific pitting corrosion rate and the levels of inclusions and carbonitrides of the corrosion-resistant alloy prepared in Example 2 under the conditions of corrosion time of 24 h and corrosion temperature of 22±2° C. are shown in Table 4 below:
[0085]
[0086] Table 4
[0087] The metallographic diagram of the corrosion-resistant alloy prepared by the process of the present invention is as follows: Figures 1 to 3 shown.
Claims
1. A production process for a high-purity, pitting-resistant Ni-Fe-Cr-Mo-Cu-based corrosion-resistant alloy, characterized in that: The following steps are involved: S1. Determine the composition control point of the corrosion-resistant alloy; S2. The raw materials are smelted in an electric furnace + AOD furnace + LF furnace to obtain φ250-430mm electrode blanks; S3. The electrode blank is remelted by electroslag in a protective atmosphere, and the electroslag ingot with a diameter of 360-590 mm is obtained by constant melting rate electroslag.
2. The production process of a high-purity, pitting-resistant Ni-Fe-Cr-Mo-Cu based corrosion-resistant alloy according to claim 1, characterized in that: The composition control points in step S1 are specifically: the control elements simultaneously satisfy Cr+3.3Mo+0.25Ni≥41.5, C≤0.015%, and N≤100ppm.
3. The production process of a high-purity, pitting-resistant Ni-Fe-Cr-Mo-Cu based corrosion-resistant alloy according to claim 1, characterized in that: The raw materials in step S2 include the following components in weight percentage: Cr22.8-23.2%, Ni38.8-39.2%, Mo3.0-3.2%, Cu1.8-2.2%, C≥2.0%, P≤0.025%.
4. The production process of a high-purity, pitting-resistant Ni-Fe-Cr-Mo-Cu based corrosion-resistant alloy according to claim 1, characterized in that: The step S2 specifically includes the following steps: S21. Electric furnace smelting: adjust C to ≥ 2.00%; S22.AOD furnace smelting: Blow oxygen until C≤0.006% and then reduce, adjust each element to the internal control range; S23.LF furnace smelting: Al wire and Al powder are used as deoxidizers for deoxidation; Ar gas is used for stirring during smelting, and Ca wire is inserted at 3 meters / ton before steelmaking; casting is carried out after the composition is qualified, and the casting temperature is controlled at 1500-1530℃ to obtain φ250-430mm electrode blanks.
5. The production process of a high-purity, pitting-resistant Ni-Fe-Cr-Mo-Cu based corrosion-resistant alloy according to claim 4, characterized in that: In the step S23, 0.5-1.0 kg of deoxidizer is added per ton of molten steel.
6. The production process of a high-purity, pitting-resistant Ni-Fe-Cr-Mo-Cu based corrosion-resistant alloy according to claim 1, characterized in that: The protective atmosphere in step S3 is Ar gas, the electroslag adopts a 5-component slag system, the slag system is CaF2:Al2O3:CaO:MgO:TiO2=50:22:20:5:3, and the slag system controls C≤0.03%; the melting rate of the φ360mm electroslag ingot is controlled at 5.5±0.5kg / min, the melting rate of the φ480mm electroslag ingot is controlled at 6.5±0.5kg / min, and the melting rate of the φ590mm electroslag ingot is controlled at 8±0.5kg / min.
7. The production process of a high-purity, pitting-resistant Ni-Fe-Cr-Mo-Cu based corrosion-resistant alloy according to claim 1, characterized in that: The step S3 further includes the following steps: S4. The electroslag ingot is prepared into the required specifications by forging or rolling, and is subjected to a solid solution treatment at 980°C to obtain a high-purity, pitting-resistant Ni-Fe-Cr-Mo-Cu based corrosion-resistant alloy.